2013
DOI: 10.1134/s0012496613040054
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of microtubules in the effects of glutoxim and molixan on the intracellular concentration of Ca2+ in macrophages

Abstract: 196Currently, a great number of disulfide containing drugs altering the redox status and having a physiolog ically significant effect on cells have been developed and introduced into clinical practice. The pharmaceu tical agent Glutoxim®, disodium salt of oxidized glu tathione (GSSG) with a platinum nanoadditive (PHARMA VAM, Moscow, Russia) is used as an immunomodulator and a hemostimulant in the inte grated therapy of bacterial and viral diseases, psoriasis, as well as radio and chemotherapies of cancer [1]. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…Thus in T lymphocytes with defective protein WAVE2 activating the Arp2/3 complex one observes suppression of store dependent Ca 2+ entry activated by thapsigargin [22]. The above results, along with our previous findings [2][3][4][5][6][7][8][9][10][11] testify about that in the action of glutoxim or molixan on [Ca 2+ ] i in macrophages the same signal proteins and their complexes as in the process of exocytosis are involved: tyrosine kinases, G proteins of small molec ular mass, mechanisms of vesicular transport; actin and tubulin cytoskeleton, and also Arp2/3 complex mediating rearrangements of the actin cytoskeleton. Reorganization of the actin cytoskeleton induced in macrophages upon action of glutoxim or molixan may also mediate activation of macrophages and alleviate processes of endo and exocytosis.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Thus in T lymphocytes with defective protein WAVE2 activating the Arp2/3 complex one observes suppression of store dependent Ca 2+ entry activated by thapsigargin [22]. The above results, along with our previous findings [2][3][4][5][6][7][8][9][10][11] testify about that in the action of glutoxim or molixan on [Ca 2+ ] i in macrophages the same signal proteins and their complexes as in the process of exocytosis are involved: tyrosine kinases, G proteins of small molec ular mass, mechanisms of vesicular transport; actin and tubulin cytoskeleton, and also Arp2/3 complex mediating rearrangements of the actin cytoskeleton. Reorganization of the actin cytoskeleton induced in macrophages upon action of glutoxim or molixan may also mediate activation of macrophages and alleviate processes of endo and exocytosis.…”
Section: Resultssupporting
confidence: 74%
“…Using a wide range of agents affecting components of intracellular signaling systems in cells, we have shown for the first time that key players in a signal cas cade triggered by GSSG and glutoxim and leading to [Ca 2+ ] i increase in macrophages are tyrosine kinases and tyrosine phosphatases [3,5], phosphatidylinositol kinases [6], key enzymes of the phosphoinositide sig nal pathway -phospholipase C and protein kinase C [7]. It was also found that the effect of glutoxim and molixan on [Ca 2+ ] i in macrophages was mediated by actin cytoskeleton [8] and microtubules [9].…”
Section: Introductionmentioning
confidence: 71%
“…The above results, along with our previous findings [2][3][4][5][6][7][8][9], also indicate that the action of glutoxim and molixan on [Ca 2+ ] i levels in macrophages involves the same signal proteins and complexes that participate in exocytosis: tyrosine kinases and tyrosine phos phatases, phosphatidylinositol 3 and 4 kinases, pro tein kinase C, small G proteins of the Ras superfamily, vesicle trafficking, and actin and tubulin cytoskeleton [15]. In addition, we have shown that glutoxim and molixan themselves induce reorganization of the actin cytoskeleton [8], which mediates macrophage activa tion and facilitates endo and exocytosis.…”
supporting
confidence: 88%
“…It was also found that the effects of glutoxim and molixan on [Ca 2+ ] i in mac rophages were mediated by actin cytoskeleton ele ments [8] and microtubules [9].…”
mentioning
confidence: 99%